N. Strejilevich, Una sola morte numerosa (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
In the book Una sola morte numerosa Nora Strejilevich shares with the reader her personal commitment to convey a painful memory, as direct witness of one of the darkest moments of the history of Argentina.